2008
DOI: 10.2747/1060-586x.24.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Securing Property in Contemporary Kyrgyzstan

Abstract: Throughout the post-Soviet region, conflicts over property feature prominently in local headlines and public debates. This article explores ownership conflicts in contemporary Kyrgyzstan by asking why some marketplaces (bazaars) have remained stable and relatively secure in an environment characterized by weak rule of law and ongoing asset redistribution. Using data from field research conducted in 2006-2007, including interviews, newspaper articles, and government documents, the article identifies historical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…36 In open-ended comments during the interviews, many of those who had given this explanation a low value on the questionnaire provided evidence which suggested that identity 34 On business elites as vital actors in opposition politics, see Radnitz (2010). 35 On the relationship between business and politics in Kyrgyzstan, and the role of the parliament as a form of bazaar, see Spector (2008). 36 Identity politics are key to an understanding of political behavior in much of the developing world.…”
Section: Identity Politicsmentioning
confidence: 97%
“…36 In open-ended comments during the interviews, many of those who had given this explanation a low value on the questionnaire provided evidence which suggested that identity 34 On business elites as vital actors in opposition politics, see Radnitz (2010). 35 On the relationship between business and politics in Kyrgyzstan, and the role of the parliament as a form of bazaar, see Spector (2008). 36 Identity politics are key to an understanding of political behavior in much of the developing world.…”
Section: Identity Politicsmentioning
confidence: 97%
“…The transformation of the legislative branch of power into an organ for protecting or generating wealth provides an instructive case. In Kyrgyzstan, Regine Spector (, 165) notes that the parliament's political power became less connected to its legislative duties than its mutation into an extra legal state body for protecting legally questionable or plainly illegal transactions through representation in the legislature.…”
Section: Why Invest?mentioning
confidence: 99%
“…Indeed, the point is precisely that this is not what happens. Instead, the argument is that divided-executive constitutions produce incentives that (unlike presidentialist constitutions) significantly complicate 97 As documented in Spector 2008;Ozcan 2010. 98 E.g., Segodnia, May 15, 2010Telekrytyka, July 12, 2010.…”
Section: Kyrgyzstan: Presidentialist Constitution and Single-pyramid mentioning
confidence: 99%